2007
DOI: 10.1016/j.foodqual.2006.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Preference study using a latent class approach. Analysis of European preferences for smoked salmon

Abstract: We present in this paper the advantages of the latent class vector model approach in the analysis of preference ratings. We illustrate the practical application of this methodology on the basis of a preference study of smoked salmons in European countries. A set of 30 samples was selected spanning the characteristic variability of cold-smoked salmon available in six European countries (Belgium, Denmark, France, Germany, Italy and the United Kingdom). Consumers from the main countries of consumption (Belgium, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 11 publications
1
22
0
1
Order By: Relevance
“…Further, Sañudo et al (2007) showed higher liking of lamb meat among consumers in countries with high traditional lamb meat consumption, and association between country and liking of different lamb types, presumably due to different culinary backgrounds. Séménou, Courcoux, Cardinal, Nicod, and Ouisse (2007) were able to show to some degree a link between the preferences of consumers from different countries and sensory characteristics of smoked salmon within their country. This indicates that the tradition of fresh fish in Iceland, but frozen in Ireland might explain the different preferences within the two countries.…”
Section: Consumer Differences By Countries and Agementioning
confidence: 94%
“…Further, Sañudo et al (2007) showed higher liking of lamb meat among consumers in countries with high traditional lamb meat consumption, and association between country and liking of different lamb types, presumably due to different culinary backgrounds. Séménou, Courcoux, Cardinal, Nicod, and Ouisse (2007) were able to show to some degree a link between the preferences of consumers from different countries and sensory characteristics of smoked salmon within their country. This indicates that the tradition of fresh fish in Iceland, but frozen in Ireland might explain the different preferences within the two countries.…”
Section: Consumer Differences By Countries and Agementioning
confidence: 94%
“…In this regard, we notice that per capita consumption of such a product in UK is only 0.12 kg, in spite of the fact that UK is the third producer of smoked salmon in Europe. In addition, we recall that Sémenou et al [32] studied consumer behaviour across various European countries and highlighted that Italian consumers place great importance on product appearance (the orange colour and the translucent appearance) rather than on spoilage indicators confirming that Italian consumers are generally less trained to taste smoked salmon.…”
Section: An Empirical Applicationmentioning
confidence: 74%
“…Moreover, it has an intense orange and homogeneous colour, translucent appearance, low odour, firm and crunchy texture. The sensometric study proved that PRO19 is generally less appreciated than PROD24 [32].…”
Section: An Empirical Applicationmentioning
confidence: 93%
“…Besides non-automatic, but visual, clustering rules , or probabilistic approaches (De Soete & Winsberg, 1993;Séménou, Courcoux, Cardinal, Nicod, & Ouisse, 2007), k-means clustering or hierarchical clustering methods are the most common approaches. The k-means clustering, as the fuzzy clustering (c-means), are partitioning methods that may be considered as non-probabilistic versions of the model-based methods.…”
Section: The Clustering Of Variables Around Latent Variables (Clv) Mementioning
confidence: 99%